Supporting municipalities in implementing participatory development initiatives: lessons learned from a decade of Poverty Stoplight implementations: Apoyo a los municipios en la implementación de iniciativas de desarrollo participativo: Lecciones aprendidas de una década de implementación del Semáforo de Eliminación de Pobreza - Burt, Marie Claire; Parwani, Karuna; Ramos, Nancy; Peroni, Victoria; Pane, Juan Carlos; Burt, Martin (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2023)
Participatory initiatives in local governance, such as participatory budgeting and local assemblies, aim to involve communities at various levels of a development project. A key challenge remains in equipping government officials with tools to effectively understand and address community needs. This paper examines the efficacy of the Poverty Stoplight (Stoplight or PS), a participatory tool, in addressing this gap. This tool enables communities to self-assess their poverty status, identifying themselves as "red", "yellow", or "green" based on a range of indicators. Emphasizing self-assessment and mentoring, the Stoplight approach fosters community ownership and agency. This ensures members play a pivotal role in highlighting their needs and forming their development aspirations. This research adopts a case study approach, detailing experiences with the Poverty Stoplight across diverse contexts, such as in Paraguay and Ecuador. Results indicate that the Stoplight not only facilitates individual poverty elimination strategies but also promotes collective participation within local governmental structures.